Sistem Perekrutan Marketplace Guru terhadap Nasib Guru Honorer di Indonesia - Zidan, Muhammad Zainuddin (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2024)
This article discusses the teacher recruitment system in the Teacher Marketplace, with a focus on the fate of contract teachers, which was a policy introduced by Nadiem Anwar Makarim during his tenure as the Minister of Education, Culture, Research, and Technology. The system is expected to address the issues faced by contract teachers, particularly in terms of their well-being. The research method employed is qualitative, involving a literature review using primary sources from journals related to the Teacher Marketplace and secondary sources from online news reports. Although the Teacher Marketplace system is expected to expedite real-time teacher recruitment, the large number of teachers in Indonesia still leads to an imbalance in the required positions. This argument aligns with the findings of the research conducted by Hidayat and Asriyantini (2020) and contradicts those of Rosmi (2019).